Pengaruh Advertising dan Virtual Item Value terhadap Purchase Decision pada Game Roblox - Shelomita Joanna Siregar; Annisa Lutfia; Ivan Putranto (Indo Publishing, 2026)
This study aims to analyze the influence of advertising and virtual item value on purchase decisions in the Roblox game. The study is motivated by the rapid growth of the virtual economy in the gaming industry, where advertising strategies and players’ perceptions of virtual item value are considered factors that may influence purchasing decisions. This research employed a quantitative approach using a survey method. The population consisted of Roblox players who had previously purchased virtual items, while the sample comprised 130 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that advertising has a positive and significant effect on purchase decisions in Roblox. Virtual item value also has a positive and significant effect on purchase decisions in Roblox. Simultaneously, advertising and virtual item value have a positive and significant effect on purchase decisions in Roblox.